2005
DOI: 10.1152/physiolgenomics.00001.2005
|View full text |Cite
|
Sign up to set email alerts
|

Signature patterns of gene expression in mouse atherosclerosis and their correlation to human coronary disease

Abstract: The propensity for developing atherosclerosis is dependent on underlying genetic risk and varies as a function of age and exposure to environmental risk factors. Employing three mouse models with different disease susceptibility, two diets, and a longitudinal experimental design, it was possible to manipulate each of these factors to focus analysis on genes most likely to have a specific disease-related function. To identify differences in longitudinal gene expression patterns of atherosclerosis, we have devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
78
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(83 citation statements)
references
References 60 publications
4
78
1
Order By: Relevance
“…However, the absence of immune and inflammatory mediators was still evident, and, accordingly, pathways related to the inflammatory and immune responses were not significantly affected (data not shown). Next, we focused the analysis on expression of transcripts coding for major cytokines and chemokines that had been related to progression of atherosclerosis or development of more‐severe plaque phenotypes 16, 28, 29, 30, 31. As seen in Figure 5A, in both WD groups, the levels of most transcripts coding for interleukins or for CC or CXC cytokines were very close or within ≈1‐fold change of the levels observed in the CHOW group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the absence of immune and inflammatory mediators was still evident, and, accordingly, pathways related to the inflammatory and immune responses were not significantly affected (data not shown). Next, we focused the analysis on expression of transcripts coding for major cytokines and chemokines that had been related to progression of atherosclerosis or development of more‐severe plaque phenotypes 16, 28, 29, 30, 31. As seen in Figure 5A, in both WD groups, the levels of most transcripts coding for interleukins or for CC or CXC cytokines were very close or within ≈1‐fold change of the levels observed in the CHOW group.…”
Section: Resultsmentioning
confidence: 99%
“…From a molecular point of view, gene expression patterns in mouse aortas that defined different stages of atherosclerosis development also correlated with severity of human coronary lesions 16. Like in humans, atherosclerosis development in apoE −/− mice is driven by hypercholesterolemia, and plasma cholesterol levels and the extent of lesion development are directly related to the cholesterol content in their diet 17.…”
Section: Introductionmentioning
confidence: 98%
“…To address this, comparison statistics (eg, t test, 19,21,13,15 ANOVA, 17 Wilcoxon ANOVA 19 ) need to be used to assign a confidence level to the differential expression. These statistics require replicates and use the variability within the replicates to assign a probability value that indicates the probability of incorrectly classifying a gene as differentially regulated.…”
Section: Statistical and Bioinformatical Analysismentioning
confidence: 99%
“…At present, however, there is no consensus about the best method to correct for multiple testing in microarray experiments. To this end, 5 recent studies have used permutation-based methods: significance analysis of microarrays 37 (SAM), 13,21 custom-made analysis algorithms including permutations to study multiple sets of time-course microarray data, 9,13 or by comparison with randomized data sets to quantify false-positive frequency in the data sets. 26 The statistical techniques discussed above aim to identify genes that are differentially expressed on a gene-by-gene basis.…”
Section: Statistical and Bioinformatical Analysismentioning
confidence: 99%
“…Carefully designed studies have revealed genes capable of identifying different stages of atherosclerotic disease in human aortas, the SNPs for which may be useful for genomic classification of patients with clinical implications (Seo et al 2004). Extending this type of approach, combined results from microarray experiments using mouse atherosclerosis models and human coronary gene expression datasets have also identified a shared group of genes for classifying disease stage (Tabibiazar et al 2005). These classifier genes were able to distinguish between native coronary artery disease and in-stent restenosis.…”
Section: Discussionmentioning
confidence: 99%